(untitled) (Práxis Educativa, 2024)
Adult education takes place in various contexts. Prisons are one of them. Therefore, in this article, the aim is essentially to outline the profile of teachers who work in prisons in Portugal and, at the same time, to understand how they build and develop the knowledge that enables them to carry out their duties in a place with such particular characteristics. To this end, a national survey of teachers working in education in prisons on the mainland and islands, to whom a questionnaire survey was sent, was carried out. The results show, among other aspects, that they are mainly women, that most of them are over 40 years old, that there is a predominance of university graduates, that they have no specific training to teach adults in prisons and that the work context and the practice carried out in it is important in building the knowledge that allows them to work in such a context. Keywords: Education in prisons. Teachers. Knowledge.